First report of a subacute stent thrombosis in a prasugrel resistant patient successfully managed with ticagrelor. (December 2014) - Fiore, Mathieu; Horovitz, Alice; Pons, Anne-Cecile; Leroux, Lionel; Casassus, Frederic
Abstract Prasugrel is a widely used antiplatelet agent in the setting of percutaneous coronary intervention. In case of resistance to this third-generation thienopyridine, choices of alternative drugs remain limited. Here, we describe a case of a 49-year-old man with stent thrombosis occurring 5 days after drug-eluting stent implantation despite a well-conducted antiplatelet therapy with aspirin and prasugrel. Evaluation of platelet functions by different tests revealed prasugrel resistance. Genotyping for various CYP single-nucleotide polymorphisms showed that the patient carried mutant alleles encoding enzymes CYP2B6 and CYP2C9 involved in prasugrel metabolic pathway. Strikingly, an adequate platelet response was rapidly obtained after switching from prasugrel to ticagrelor.